Metode Dakwah Pondok Pesantren dalam Menanggulangi Radikalisme - Rosidi, Rosidi (BINA' AL-UMMAH, 2012)
Research on Islamic boarding schools and radicalism is important to be done, conidering the events of terror and anarchy invariuos places of Indonesia such as in Solo, Madura, Jakarta and Cirebon, done by people who have a relationship with the Islamic boarding schools. This research tried to be explore the opinion of one of the existing Islamic boarding schools in Lampung: Al hikmah boarding school in Bandar Lampung about the radical even that were the religious activities have been done againts radicalism? Data in this research were collected through interviews, observation, and documentations. Data compiled then analyzed by employing qualitative approach and the critical method by comparing related theories and the experts opinions. The findings of this study indicated that radicalism had no relationship with religious factors, and nor to Islamic boarding schools, even if it was just to a person. The main factor actually of economic competition, the excessive fanaticism, juvenile delinquency and employment. In addition to these factors radicalisme caused by lack of education and lack of appropriate understanding and religious practice. To reduce a variety of anarchy actions al-Hikmah boarding school has conducted various activities such as educating people culture of peace, respecting each other through various activities. Students of this school were educated social life and preaching Islam peacely.